PREDICTION OF THE CHIMTEPPA EARTHQUAKE OF 1966 AND THE GISSAR EARTHQUAKE OF 1989 - Gubin I.Ye. (My University, 1990)
The earthquake discussed occurred in Tajikistan, along the southern boundary of the Gissar Valley. In 1980, I have emphasized that in detailed, large-scale seismic zoning for the purpose of planning earthquake-resistant buildings and structures one must show, for each seismic zone, not only the magnitude and intensity of the strongest probable earthquakes, but also the points of probable seismically-induced slides and dislocations. The landslides associated with the Gissar earthquake of 1989 shocked the entire country. They demonstrated once again that no construction should be undertaken without considering local geological and seismic conditions. It should be the invariable practice and a legal requirement for builders to obtain sound multifactor seismic zonation maps from scientists.